2019
DOI: 10.3390/nu11040781
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Non-Celiac Gluten Sensitivity in Brazil: Translation, Cultural Adaptation, and Validation of Italian Questionnaire

Abstract: This study aimed to translate, culturally adapt, validate, and apply a questionnaire to the Brazilian non-celiac gluten sensitive (NCGS) population. We also aimed to estimate the prevalence of symptoms which affect Brazilian NCGS. The Brazilian Portuguese version of the NCGS questionnaire was developed according to revised international guidelines. Five-hundred-and-fourty-three participants responded the NCGS questionnaire. We evaluated the reproducibility and validity of the questionnaire which presents valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…In agreement with previously performed studies, females present lower HRQoL than males, in the present study, females’ scores for the CDQ were significantly lower than those in the emotional and gastrointestinal domains as the general HRQoL [ 14 , 33 ]. Some studies showed that lower QoL among women is mainly associated with the distress caused by daily life restrictions and perceive a higher burden than expressed by males [ 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previously performed studies, females present lower HRQoL than males, in the present study, females’ scores for the CDQ were significantly lower than those in the emotional and gastrointestinal domains as the general HRQoL [ 14 , 33 ]. Some studies showed that lower QoL among women is mainly associated with the distress caused by daily life restrictions and perceive a higher burden than expressed by males [ 34 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…A possible limitation of this study may be that our sample had a higher proportion of female respondents (88.7%). However, other studies with gluten-related disorders from other countries also exhibited this trend, with over 70% of female respondents [ 2 , 14 , 32 , 33 ]. Previous studies on HRQoL of celiac patients performed in the Argentinian population showed as high as 90% of female respondents [ 20 ].…”
Section: Discussionmentioning
confidence: 82%
“…Certainly, this is the lowest prevalence rate of GRD ever reported among survey-based studies carried out in Latin American countries and elsewhere [9,10,13,14]. Despite these findings, the main gastrointestinal and extra-intestinal symptoms informed by those who met criteria for SR-GS were the same as those reported in different populations [9,10,13,14] including a Brazilian population suspected of NCGS [27]. Overall, these data highlight the need for further population-based epidemiological studies preferentially including serology tests, HLA-typing (Human Leucocyte Antigen-typing), intestinal biopsies and an in-depth questionnaire.…”
Section: Discussionmentioning
confidence: 62%
“…Unspecified modified starch was used in 33.3% (n = 4) of the samples, two samples of GFB (2, 3), and two of WGFB (2,3). All of the gluten-free bread samples combined a minimum of two starch sources, with the combination of cassava and corn starches the most frequent one, and rice flour being the third most used ingredient.…”
Section: Resultsmentioning
confidence: 99%
“…They believe in the potential health benefits of GFDs, despite the lack of scientific evidence related to such practice [6][7][8][9][10]. Therefore, the estimation is that about 10% of the world population (with or without GRD) has adopted a GFD [2,3,11,12].…”
Section: Introductionmentioning
confidence: 99%